LATEST TRENDS IN CONTINGENCY ANALYSIS OF POWER SYSTEM - VinayP.Doshi; Sadanand A. Salgar; Prof.Shravan Kumar Akireddy (International Journal of Innovations in Engineering Research and Technology, 2021)
Contingency plans based on N - 1 and N - 2 contingencies are already very much used by utilities . Artificial intelligent methods are new trends for analysing the contingency scenario along with state of art congestion management. This gives extra backup and b oost to reliable operation under contingent scenario of power system. This paper envisages the summary of all those efforts.